A seminar on ethnics relation - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
7 March 2012. In order to expose students to issues of national security, and to provide students with a platform for exchange of ideas, the Human Sciences Department of CMLHS organized an Ethnic Relations Seminar on 3 March 2012.